Convergence in Wavelet Collocation Methods for Parabolic Problems (Journal of Partial Differential Equations, 2019)
This paper studies the second-generation interpolating wavelet collocationmethods in space and different Euler time stepping methods for parabolic problems.The convergence and stability are investigated. The operators are formulated usingan efficient and exact formulation. The numerical results verify the efficiency of themethods.